Observation and Numerical Simulation of Cavity Mode Oscillations Excited by an Interplanetary Shock. Issue 3 (15th March 2018) - Takahashi, Kazue; Lysak, Robert; Vellante, Massimo; Kletzing, Craig A.; Hartinger, Michael D.; Smith, Charles W.
Abstract: Cavity mode oscillations (CMOs) are basic magnetohydrodynamic eigenmodes in the magnetosphere predicted by theory and are expected to occur following the arrival of an interplanetary shock. However, observational studies of shock‐induced CMOs have been sparse. We present a case study of a dayside ultralow‐frequency wave event that exhibited CMO properties. The event occurred immediately following the arrival of an interplanetary shock at 0829 UT on 15 August 2015. The shock was observed in the solar wind by the Time History of Events and Macroscale Interactions during Substorms‐B and ‐C spacecraft, and magnetospheric ultralow‐frequency waves were observed by multiple spacecraft including the Van Allen Probe‐A and Van Allen Probe‐B spacecraft, which were located in the dayside plasmasphere at L ∼1.4 and L ∼ 2.4, respectively. Both Van Allen Probes spacecraft detected compressional poloidal mode oscillations at ∼13 mHz (fundamental) and ∼26 mHz (second harmonic). At both frequencies, the azimuthal component of the electric field ( E ϕ ) lagged behind the compressional component of the magnetic field ( B μ ) by ∼90°. The frequencies and the E ϕ ‐ B μ relative phase are in good agreement with the CMOs generated in a dipole magnetohydrodynamic simulation that incorporates a realistic plasma mass density distribution and ionospheric boundary condition. The oscillations were also detected on the ground by the European quasi‐Meridional Magnetometer Array, which was located near the magnetic field footprints of the Van Allen Probes spacecraft. Key Points: An interplanetary shock excited magnetospheric ULF oscillations The oscillations were observed in the dayside plasmasphere by Van Allen Probes The oscillations exhibited properties consistent with cavity mode oscillations